Elaboração e validação de um instrumento de avaliação da disfagia orofaríngea na paralisia cerebral - Bentim, Claudia Cristina Ramos Granja [UNESP] (2015)
Validated instruments are not frequent in the area of oropharyngeal dysphagia, especially in the pediatric population affected by Cerebral Palsy (CP). Therefore, this study is justified by the scientific and technical deficit that permeates the scenario not only of the diagnosis of paediatric neurogenic dysphagia, but also of the principles (or variables) that determine therapeutic procedures. This study aimed at developing and validating the content and the response process of an assessment tool for paediatric oropharyngeal dysphagia in PC. Step 1 of the study was divided into literature review (1a) to check the frequency of the data; (1b) collection of information from clinical experience of 190 medical records of an institution specialized in the care of individuals with PC; (1c) analysis by the panel of specialists to choose the parameters and assigning the level of importance for each parameter using a scale of 0 to 10. The Stage 1 was completed with the development of the first version of the instrument by the panel of specialists and structuring the application manual. Step 2 included evidence of validity based on the content through the assessment and advice of a committee composed of 19 judges with expertise in neurogenic oropharyngeal dysphagia, and analysis and compilation of the results by the committee of experts, culminating in the development of the second version and electronics of the instrument. To layer the opinion of the judges a Content Validity Index (CVI) was calculated, finding the percentage of agreement. To obtain the universal consensus, IVC-UA (universal agreement), the percentage of parameters and items with CVI greater than 80% was calculated and the average agreement (IVC-Medium) was made up. Step 3 consisted of validity evidence based on the response process through a structured tool performed by 7 audiologist applicators. The comprehensibility and applicability of the questions were analyzed quantitatively...